METAL-SILICATE PARTITIONING AND THE INCOMPATIBILITY OF S AND SI DURING CORE FORMATION - Kilburn M.R.; Wood B.J. (My University, 1997)
We have determined the partitioning of a number of siderophile and lithophile elements between liquid metal and liquid silicate phases under the high temperature, low pressure conditions at which core segregation is considered to have originated . Oxygen fugacity was varied from 2 to 6 log units below the iron-wustite (IW) buffer by increasing the Si content of the metallic phase from 100 ppm up to the 8% proposed by Allegre et al. as being cosmochemically required in the earth's core. We find that Si and S, two of the principal candidates for the light element in the core are mutually exclusive in the metal phase. As oxygen fugacity is reduced, Si becomes increasingly siderophile and S increasingly lithophile. At 8% Si in the metal, all S, up to at least 1%, enters the coexisting ultramafic liquid. Thus, Si and S are incompatible during a single-stage low pressure core formation event. Mn and Cr, which are lithophile under oxidising conditions, become slightly siderophile if there is 8% Si in the metal, corresponding to an oxygen fugacity of about 6 log units below the iron-wustite (IW) buffer. Ti remains lithophile even under these conditions, only becoming siderophile at about 7 log units below IW. These results demonstrate that the Mn and Cr contents of the core proposed in , coupled with lithophile behaviour of Ti, are consistent with core segregation under strongly reducing conditions. Such conditions could not generate a core containing 2% S, however, and the problem of the high contents of oxidised Fe, Ni, Co and other siderophile elements in the mantle would remain. The only plausible way of introducing S into the core is to add it as part of a late-stage accretion of oxidised material to the earth. A second, minor phase of core segregation under oxidising conditions would supply S, but no additional Si, to the core.
Keywords: PARTITIONING; SULFUR; SILICON; CORE